Anxiety: There is an app for that. A systematic review of anxiety apps. Issue 6 (15th May 2017) - Sucala, Madalina; Cuijpers, Pim; Muench, Frederick; Cardoș, Roxana; Soflau, Radu; Dobrean, Anca; Achimas‐Cadariu, Patriciu; David, Daniel
Abstract : Background: Smartphones and mobile devices have become ubiquitous, and with the rapid advance of technology, the number of health applications (apps) that are available for consumers on these devices is constantly growing. In particular, there has been a recent proliferation of anxiety apps. However, there has been no review of the quality or content of these anxiety apps and little is known about their purpose, the features they contain, and their empirical support. The goal of this systematic review was to assess the commercially available anxiety apps. Methods: A list of anxiety apps was collected in January 2017, using the Power Search function of iTunes and Google Play. Of 5, 078 identified apps, 52 met our inclusion criteria (i.e., being defined as an anxiety/worry relief app, and offering psychological techniques aimed primarily at reducing anxiety) and were further reviewed. Results: The majority (67.3%) of the currently available anxiety apps were found to lack the involvement of health care professionals in their development, and very few (3.8%) of them have been rigorously tested. Conclusions: At the moment, although anxiety apps have the potential to enhance access to mental health care, there is a marked discrepancy between the wealth of commercially available apps, and the paucity of data regarding their efficacy and effectiveness. Although the great promise of apps is their ability to increasing access to evidence‐based mental health, the field is not quite there yet and the full potential of apps for treating anxiety has yet to be exploited.